Analysis of Corporate Taxpayer's Perceptions on the Implementation of Government Regulation No.23 of 2018 (Case Study of MSME in Pontianak City) - Budiyanto, Billy (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
The aim of this study is to understand the corporate taxpayers’ perceptions about the enactment of Government Regulation No.23 of 2018. This research use case study method and analyze 10 taxpayers’ perceptions based on interview. Findings reveal that the registration process is running smoothly. The online e-billing making process is very easy, the obstacle is interference on the system. Simple payment procedures that do not complicate. Payment at once with submits the report provides convenience. Tax payments do not disturb business entities’ production and trade process. The imposition of tariff does not see the taxpayer’s ability, so it did not provide tax justice. Government Regulation No.23 of 2018 provides tax convenience and fulfill economic requirement, but did not provides tax justice.